Palliative Prognostic Index Validation in Hospitalized Advanced Cancer Patients in Indonesia Tertiary Hospitals - Hamzah Shatri; Abigail Prasetyaningtyas; Rudi Putranto; Ikhwan Rinaldi (Interna Publishing, 2022)
Background: Accurate prediction of survival is important for advanced cancer patients to determine medical interventions plan the patient's lives and prepare for their death. The palliative prognostic index (PPI) is most popular scores used worldwide to predict life expectancy in advanced cancer palliative patients. The purpose of this study was to test validity and the performance of PPI in Cipto Mangunkusumo Hospital as a Tertiary Referral Nasional Hospital. Methods: This retrospective cohort study, uses total subject during study with consecutive sampling. Palliative prognostic index was assessed by a palliative care team (PCT). Demographic data were summarized as n (%) and Chi square for categorical variables and median or mean for continuous variables. Overall survival was calculated using the Kaplan-Meier method with hazard ratios. The performance of PPI analyzed using SPSS version 20.0, includes for Receiving Operator Characteristics (ROC) and Hosmer-Lemeshow calibration test. Results: 160 patients were included in the PPI study. The subjects  have an average age of 50.08 years and are mostly women 68.10%. 28 (17.50%) had symptoms of dyspnoea, 22 (14.60%) pneumonia, and 19 (11.90%) had pain. The number of patients who died during hospitalisation was 83 (51.90%). PPI sum score >6  109 (68,10%). Calibration performance PPI score reached x2 = 8.915 (p = 0.259), and showed correlation  r 0.799 (p 0.000). The accuracy of PPI scores in predicting survival in advanced cancer patients in studies for survival <3 weeks 81%, with a sensitivity of 85%, specificity 70%, PPV 86%, and NPV 67%. Predictive accuracy of survival within 3-6 weeks had 76%, sensitivity 66%, specificity 88%, PPV 85% and NPV 70%. PPI score discrimination performance is had a AUC value of 0.822 (95% CI 0.749-0.895). Conclusion: Palliative Prognostic Index (PPI ) is valid and has good performance in predicting the survival of advanced cancer patients and may  be used to help clinicians in palliative care consultation.